Heterostructured ZnFe2O4/Fe2TiO5/TiO2 Composite Nanotube Arrays with an Improved Photocatalysis Degradation Efficiency Under Simulated Sunlight Irradiation - Xiong, Kun; Wang, Kunzhou; Chen, Lin; Wang, Xinqing; Fan, Qingbo; Courtois, Je´re´mie; Liu, Yuliang; Tuo, Xianguo; Yan, Minhao (Nano-Micro Letters, 2017)
To improve the visible light absorption and photocatalytic activity of titanium dioxide nanotube arrays (TONTAs), ZnFe2O4 (ZFO) nanocrystals were perfused into pristine TONTA pipelines using a novel bias voltage-assisted perfusion method. ZFO nanocrystals were well anchored on the inner walls of the pristine TONTAs when the ZFO suspensions (0.025 mg mL−1) were kept under a 60 V bias voltage for 1 h. After annealing at 750 °C for 2 h, the heterostructured ZFO/Fe2TiO5 (FTO)/TiO2 composite nanotube arrays were successfully obtained. Furthermore, Fe3+ was reduced to Fe2+ when solid solution reactions occurred at the interface of ZFO and the pristine TONTAs. Introducing ZFO significantly enhanced the visible light absorption of the ZFO/FTO/TONTAs relative to that of the annealed TONTAs. The coexistence of type I and staggered type II band alignment in the ZFO/FTO/TONTAs facilitated the separation of photogenerated electrons and holes, thereby improving the efficiency of the ZFO/FTO/TONTAs for photocatalytic degradation of methylene blue when irradiated with simulated sunlight. Highlights: 1 ZnFe2O4 nanocrystals were perfused into pristine TiO2 nanotube array pipelines using a novel bias voltage-assisted perfusion method. 2 Novel heterostructured ZnFe2O4/Fe2TiO5/TiO2 composite nanotube arrays were obtained with staggered type II band alignment at the ZnFe2O4/Fe2TiO5 interface and type I band alignment at the Fe2TiO5/TiO2 interface. 3 Visible light absorption and the photocatalytic degradation efficiency of methylene blue were significantly improved upon irradiation with simulated sunlight.